Hemostatic efficacy, safety, and pharmacokinetics of a recombinant von Willebrand factor in severe von Willebrand disease - Gill, Joan C.; Castaman, Giancarlo; Windyga, Jerzy; Kouides, Peter; Ragni, Margaret; Leebeek, FrankW.G.; Obermann-Slupetzky, Ortrun; Chapman, Miranda; Fritsch, Sandor; Pavlova, Borislava G.; Presch, Isabella; Ewenstein, Bruce (Blood, 2015)
This phase 3 trial evaluated the safety and hemostatic efficacy of a recombinant von Willebrand factor (rVWF) for treatment of bleeds in severe von Willebrand disease (VWD). rVWF was initially administered together with recombinant factor VIII (rFVIII) and subsequently alone, as long as hemostatic factor VIII activity (FVIII:C) levels were maintained. Pharmacokinetics (PK) were evaluated in a randomized cross-over design (rVWF vs rVWF:rFVIII at 50 IU VWF:ristocetin cofactor activity [RCo]/kg). Bleed control for all treated bleeds (N = 192 bleeds in 22 subjects) was rated good or excellent (96.9% excellent; 119 of 122 minor, 59 of 61 moderate, and 6 of 7 major bleeds) on a 4-point scale (4 = none to 1 = excellent). A single infusion was effective in 81.8% of bleeds. Treatment success, defined as the number of subjects with a mean efficacy rating of <2.5, was 100%. The PK profile of rVWF was not influenced by rFVIII (mean VWF:RCo terminal half-life: 21.9 hours for rVWF and 19.6 hours for rVWF:rFVIII). FVIII:C levels increased rapidly after rVWF alone, with hemostatic levels achieved within 6 hours and sustained through 72 hours after infusion. Eight adverse events (AEs; 6 nonserious AEs in 4 subjects and 2 serious AEs [chest discomfort and increased heart rate, without cardiac symptomatology] concurrently in 1 subject) were associated with rVWF. There were no thrombotic events or severe allergic reactions. No VWF or FVIII inhibitors, anti-VWF binding antibodies, or antibodies against host cell proteins were detected. These results show that rVWF was safe and effective in treating bleeds in VWD patients and stabilizes endogenous FVIII:C, which may eliminate the need for rFVIII after the first infusion. This trial was registered at www.clinicaltrials.gov as #NCT01410227. •rVWF:rFVIII is safe and hemostatically effective in severe VWD patients for a variety of bleeding symptoms.•rVWF induces sustained stabilization of endogenous FVIII, which could obviate the need for rFVIII after the first infusion.